2015
DOI: 10.1002/bit.25615
|View full text |Cite
|
Sign up to set email alerts
|

More similar than different: Host cell protein production using three null CHO cell lines

Abstract: To understand the diversity in the cell culture harvest (i.e., feedstock) provided for downstream processing, we compared host cell protein (HCP) profiles using three Chinese Hamster Ovary (CHO) cell lines in null runs which did not generate any recombinant product. Despite differences in CHO lineage, upstream process, and culture performance, the cell lines yielded similar cell-specific productivities for immunogenic HCPs. To compare the dynamics of HCP production, we searched for correlations between the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
48
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 50 publications
(79 reference statements)
11
48
1
Order By: Relevance
“…These results suggest that, while final drug product HCP profiles are influenced by the innate identities and abundances of the host cell, many important differences exist. Given the findings herein plus recent results that showed high similarity between proteomic profiles of different null CHO cell lines and upstream processes, 44 variations in downstream processes are likely the primary cause of the significant differences we observed for final drug product HCP profiles as certain proteins will be more effectively purified than others (depending on the downstream process employed).…”
Section: Wwwtandfonlinecomsupporting
confidence: 50%
“…These results suggest that, while final drug product HCP profiles are influenced by the innate identities and abundances of the host cell, many important differences exist. Given the findings herein plus recent results that showed high similarity between proteomic profiles of different null CHO cell lines and upstream processes, 44 variations in downstream processes are likely the primary cause of the significant differences we observed for final drug product HCP profiles as certain proteins will be more effectively purified than others (depending on the downstream process employed).…”
Section: Wwwtandfonlinecomsupporting
confidence: 50%
“…Hence, bacterial HCPs have the potential to influence the immunogenicity of the biotherapeutic by having adjuvant‐like activity. HCP contamination is also an issue for mammalian cell expression systems 6, 12, 13. However, non‐mammalian HCPs are more likely to pose a risk in patients, compared with their mammalian counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…PLBL2 was identified and quantified in HCCF, with the Top 3 strategy 19 using a 4-point calibration curve of spiked internal standard protein (bovine carbonic anhydrase II). Table 1 shows the quantitation results obtained by DIA SWATH MS and by a PLBL2-specific ELISA 25 in five HCCF samples. Results showed that the measured PLBL2 levels by DIA SWATH MS quantification agreed well with those from an orthogonal analysis by PLBL2-specific ELISA ( Table 1).…”
Section: D Uhplc-ms/ms Strategies For Absolute Quantitation Of Hcps mentioning
confidence: 99%
“…This molar concentration was then normalized by the MW ratio of the HCP to the bovine carbonic anhydrase II to calculate the ppm level of these HCPs. Similarly, PLBL2 molar concentration was determined using the 4-point standard curve generated from the Top 3 peak area data of bovine carbonic anhydrase II, which was then converted to the mg/mL to compare with ELISA 25 results. Carbonic anhydrase II peptides used for quantification were unique to the bovine sequence of the protein.…”
Section: Quantitative Analysis Of Data Independent Swath Ms and Prm Datamentioning
confidence: 99%